Inscribed gestures: the vernacular-cosmopolitan dynamic of sign language in Michael Roes's novel Die Laute. Issue 5 (3rd May 2020) - Huss, Markus
ABSTRACT: How can sign language be rendered in written literary form? What can such a literary rendering teach us about the social dimensions and aesthetic productivity of a language, which in this case demands intermedial translation? How does the thematisation and use of sign language play into the vernacular-cosmopolitan dynamic of world literature? The essay addresses these questions by turning to the German author and ethnographer Michael Roes's Die Laute (2012). In this novel, a young Yemenite musical genius, Aziz, loses his hearing and is forced to learn the local variety of sign language in the city of Aden. The characterisation of sign language is shown to oscillate between two poles: as a uniform linguistic entity, beyond any specific international, national or subnational framework, and as a variety of vernacular practices, linked to specific socio-geographical spaces. The analysis displays how the novel's metalinguistic reflections on the specificities of sign language on part of the protagonist prompts the reader to consider the text as a translation of a sign language original. Sign language in terms of a vernacular, ritualized practice, is shown to be used as a tool for aesthetic renewal, inviting the reader to imagine sign language as poetic practice.